The Security Aspect of Turkey-United States Relations: In Search For a New Model - Irina A. Svistunova (Vestnik MGIMO-Universiteta, 2016)
Security cooperation has always been an important aspect of the relations between Turkey and the USA. In Cold War era Turkish-American interaction within NATO played a crucial role in this cooperation. After that period the two countries began to search for a new model of their relations. Both Turkey and the USA started to use cooperation within NATO for the purpose of strengthening their global positions. At the same time the USA aspiration to use military bases in Turkey beyond NATO obligations frequently becomes a source of disagreement and crises in the relations of the two countries as it happened during the American intervention to Iraq in 2003. At present new challenges for regional security, especially in the Middle East, demands new forms of interaction between Turkey and the USA. The beginning of "the Arab spring" was met in Ankara and Washington with overlapping interest in changing conservative regimes and promoting "Turkish model". At the same time such questions as participation of Turkey in the fight against ISIL and the USA military cooperation with the Syrian Kurds, whom Ankara considers to be connected with the PKK terrorist organization, has brought serious contradictions between the two countries. The cause of these contradiction is the difference in the perception of threats in Turkey and in the Western countries. While the search for new forms of security cooperation meets with difficulties, NATO remains important for the relations between Turkey and the USA, despite traditionally high level of anti-NATO moods in the Turkish society.